Sehat Tanpa Kanker Dengan Upaya Preventif Melalui Edukasi Dan Pemeriksaan Laboratorium Di Kampung Sidomulyo Rw 06 Kel. Bener, Kec. Tegalrejo Yogyakarta - Nuryani, Siti; Harmilah, Harmilah; Suyono, Suyono; Kurniati, Eni; Sudaryanto, Sigit; Kasiyati, Menik (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The community receives guidance and counseling about health and can develop a relationship with health initiatives, this can be designed in a higher education community with various activities that can contribute to community health. The purpose of PkM is to find out the knowledge of residents about cancer and to know Health through simple laboratory examinations through Preventive activities with education and Healthy Laboratory examinations in Sidomulyo Village RW 06 Kel. Bener, Tegalrejo District, Yogyakarta. The method used in the delivery is the lecture or counseling method to increase knowledge through pretests and posttests in measuring health status with general health examinations, and simple laboratory examinations. Residents of Sidomulyo Village, Bener Village, Tegalrejo District, Yogyakarta have never had counseling related to cancer in the past few years, and how much knowledge is not yet known. Based on this, it is necessary to hold counseling activities. Lecturers have the opportunity to carry out the Tri Dharma of Higher Education in the form of Community Service (PkM). The results of the activity are the implementation of PkM activities and increased knowledge about cancer. In addition, from 27 residents who were examined, it was found that 30% had high uric acid levels, 11% had high random blood sugar levels, 37% had high uric acid levels and 90% had high cholesterol.